Vitamin D Receptor Deficiency Enhances Wnt/β-Catenin Signaling and Tumor Burden in Colon Cancer - Larriba, María Jesús; Ordóñez-Morán, Paloma; Chicote, Irene; Martín-Fernández, Génesis; Puig, Isabel; Muñoz, Alberto; Pálmer, Héctor G. (PLOS ONE, 2011)
Aberrant activation of the Wnt/β-catenin pathway is critical for the initiation and progression of most colon cancers. This activation provokes the accumulation of nuclear β-catenin and the induction of its target genes. Apcmin/+ mice are the most commonly used model for colon cancer. They harbor a mutated Apc allele and develop intestinal adenomas and carcinomas during the first months of life. This phenotype is caused by the mutation of the second Apc allele and the consequent accumulation of nuclear β-catenin in the affected cells. Here we describe that vitamin D receptor (VDR) is a crucial modulator of nuclear β-catenin levels in colon cancer in vivo. By appropriate breeding of Apcmin/+ mice and Vdr+/− mice we have generated animals expressing a mutated Apc allele and two, one, or none Vdr wild type alleles. Lack of Vdr increased the number of colonic Aberrant Crypt Foci (ACF) but not that of adenomas or carcinomas in either small intestine or colon. Importantly, colon ACF and tumors of Apcmin/+Vdr-/- mice had increased nuclear β-catenin and the tumors reached a larger size than those of Apcmin/+Vdr+/+. Both ACF and carcinomas in Apcmin/+Vdr-/- mice showed higher expression of β-catenin/TCF target genes. In line with this, VDR knock-down in cultured human colon cancer cells enhanced β-catenin nuclear content and target gene expression. Consistently, VDR depletion abrogated the capacity of 1,25(OH)2D3 to promote the relocation of β-catenin from the nucleus to the plasma membrane and to inhibit β-catenin/TCF target genes. In conclusion, VDR controls the level of nuclear β-catenin in colon cancer cells and can therefore attenuate the impact of oncogenic mutations that activate the Wnt/β-catenin pathway.